INFLUENCE OF PRE-SEED TREATMENT ON SOWING QUALITIES AND PHYTOSANITARY CONDITION OF NUTTLE SEEDS - Pospielova, G.; Kovalenko, N.; Nechiporenko, N.; Sherstiuk, O.; Morozov, O. (Scientific Progress & Innovations, 2022)
In modern conditions of agriculture in Ukraine, there is a growing need to control the phytosanitary state of seed material and its influence on seed quality. The purpose of the study is to find out the possibility of increasing the condition of chickpea seeds using poisons and microbiological preparations. Determination of laboratory germination and study of the microflora of seeds was carried out by the method of germination in a humid chamber, the substrate was filter paper and sand. The test object is chickpea grain of the Zekhavit variety of the 2020 and 2021 harvest. Pesticides of various origins were used in the experiments. Among them are FitoDoctor, Trichodermin, Biophosphorin, Maxim Advance. The control option is seeds without treatment. Low quality indicators of seed material were established. Chickpea seeds are considered to be conditioned with a laboratory germination of not less than 90%. In the years of research (2020–2021), this indicator was 70.3% and 71.0%, respectively. The grain infectivity of the 2021 harvest reached 76.4%, which is 2.9% more than in 2020. The influence of pesticides of chemical and biological origin on the level of infection of seeds with pathogenic microorganisms and the species composition of pathogens (Alternaria Nees., Fusarium Link, Botrytis Mich., Mucor Mich., Aspergillus Mich., Penicillium Link., Pseudomonas spp.) was studied. The studied drugs inhibited the development of pathogens and had a positive effect on the laboratory germination of chickpea seeds of the Zekhavit variety. Biofungicide FitoDoctor reduced the level of contamination by 20.0%, mainly due to bacterial infection. During the use of composite mixtures, tendencies of a positive effect on sowing qualities and phytosanitary condition of seeds were revealed. Fungicidal protoxin Maxim Advance showed rather weak antibacterial activity. The obtained results indicate that it is impractical to study microbiological fungicides in the conditions of a wet chamber on filter paper. With the use of a sandy substrate, 87.3% and 89.8% of conditionally healthy seedlings were obtained from the total number of germinated grains (86.5% and 87.3%). Pesticides of biological and chemical origin have shown equivalent antimicrobial effectiveness. The positive effect of biological preparations (FitoDoctor, Trichodermin) and compositions (FitoDoctor + Trichodermin and Biophosphorin + PhytoDoctor + Trichodermin) on the laboratory germination of chickpea seeds and sufficiently high biological efficiency against conditionally parasitic types of microorganisms have been proven.